Employee Performance Model Through Work Productivity: Work Professionalism and Training in PT Semen Padang - Dori Mittra Candana; Hapzi Ali; Zefriyenni Zefriyenni (Qubahan Academic Journal)
PT Semen Padang (Persero) Tbk is an established Indonesian corporation operating in the cement industry. Increased competition in the local market is projected to improve the quality of cement produced by the inflow of many new businesses into Indonesia . This research aims to identify, evaluate, and quantify the immediate and secondary impacts of professionalism, training, work productivity, and employee performance. A proportional random sampling technique was utilized to choose 296 employees from PT Semen Padang (Persero) Tbk, with the data subsequently examined using SEM-PLS. The data further reveal that professionalism moderately improves employee performance, while training considerably enhances it. Work productivity is shown to have a noteworthy positive impact on employees' productivity. Additionally, both professionalism and training serve as mediators, positively influencing employee performance due to their impact on work productivity. This study underscores the pivotal role of professionalism and training in augmenting work productivity and overall employee performance. This study underscores the pivotal role of professionalism and training in augmenting work productivity and overall employee performance. The results emphasize the significance of these factors in maintaining competitiveness in Indonesia's cement industry amidst increasing market rivalry.This research advises companies to improve professionalism and increase the intensity of training, which can provide benefits for improving employee performance.